An illustrated guide to relativity - Takeuchi, Tatsu (Cambridge, UK ; New York : Cambridge University Press, 2010)
Presents a step-by-step explanation of Einstein's Special Theory of Relativity through a series of diagrams rather than equations.
Pt. III. Dynamics: relativity with a few equations -- 10. The world's most famous equation -- 11. The problem -- 12. Newtonian dynamics -- The mass-momentum vector -- The impulse vector -- Inertial mass -- Newton's Second Law -- Newton's Third Law and the conservation of mass-momentum -- 13. Relativistic dynamics -- The energy-momentum vector -- The energy-momentum vector of a photon -- The work-impulse vector -- Conservation of energy-momentum -- E=mc2 -- Common misconception about E=mc2 -- 14. Summary of Pt. III.
Includes bibliographical references (p. [254]) and index.
Keywords: Relativity (Physics); Relativity (Physics) -- Pictorial works